POLITICILE EDUCAŢIONALE PRIN PRISMA DE GEN - REPERE FUNDAMENTALE ALE POLITICII NAŢIONALE DE ASIGURARE A EGALITĂŢII DE GEN - USM ADMIN (Moldova State University, 2009)
Education for democracy is a factor for social cohesion, mutual understanding, and solidarity, it contributes to promoting the principle of equality between men and women, and it encourages the establishment of harmonious gender relations, as well as the development of democratic society and culture.